Pengaruh Metode Pembelajaran Brainstorming Terhadap Kemampuan Pemecahan Masalah Matematis Siswa di SMP Negeri 3 Mandrehe Barat - SALOME WARUWU; Yakin Niat Telaumbanua; Sadiana Lase; Yulisman Zega (Lembaga Intelektual Muda (LIM) Maluku, 2023)
This research is based on a preliminary study conducted by researchers during observations at SMP Negeri 3 Mandrehe Barat. The problem is that students' mathematical problem-solving skills still need improvement. This study aims to determine whether there is an effect of brainstorming learning methods on students' mathematical problem-solving ability. This type of research uses the quasi-experimental research method involving two groups that are given different treatments. The population of this study was all VIII classes of SMP Negeri 3 Mandrehe Barat, and two classes were selected by simple random sampling as research samples, namely class VIII-A totaling 20 students as an experimental class taught using the brainstorming learning method and class VIII-B 21 students as a control class taught using conventional learning methods. Data were collected through student mathematical problem-solving ability tests. Based on this research, the results of hypothesis testing are and . Because > , then Ho is rejected, and Ha is accepted that there is an effect of brainstorming learning method on students' mathematical problem-solving ability at SMP Negeri 3 Mandrehe Barat.